2020
DOI: 10.1108/jbim-12-2018-0381
|View full text |Cite
|
Sign up to set email alerts
|

Impact of risk perception on customer purchase behavior: a meta-analysis

Abstract: Purpose Risk perception is an essential factor affecting how individuals evaluate risk, make decisions and behave. The impact of risk perception on customer purchase behavior has been widely studied; however, the association has been debated. Therefore, the purpose of this paper is to examine the relationship between risk perception and customer purchase behavior and to examine factors that could moderate it. Design/methodology/approach This study conducted a meta-analysis of this relationship and examined f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 81 publications
2
51
0
Order By: Relevance
“…Because almost all of the studies included in our analysis were of low or very low quality, and because of the high heterogeneity of studies in terms of anxiety, psychological flexibility, quality of life, and fear, our estimates of the effects in these areas are uncertain. As more studies emerge in the future, the long‐term effectiveness of ACT on these outcomes should be re‐examined via meta‐analysis, and an attempt should be made to explain the observed heterogeneity 57–64 …”
Section: Discussionmentioning
confidence: 99%
“…Because almost all of the studies included in our analysis were of low or very low quality, and because of the high heterogeneity of studies in terms of anxiety, psychological flexibility, quality of life, and fear, our estimates of the effects in these areas are uncertain. As more studies emerge in the future, the long‐term effectiveness of ACT on these outcomes should be re‐examined via meta‐analysis, and an attempt should be made to explain the observed heterogeneity 57–64 …”
Section: Discussionmentioning
confidence: 99%
“…Risk of bias assessment was used to evaluate the quality of the 54 studies included in the meta-analysis. Six items adapted from previously developed risk of bias instruments (Li et al 2020;Viswanathan et al 2013) were employed in this study. For each item, the response options are no, yes and unclear (Table 1).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…There is also a difference in purchasing behavior seen across levels of a country's economic development, as people have different economic abilities to buy a product (Li et al 2020). There have been studies examining the correlation between health, environmental and ethical concerns and purchase behavior in both high-income (Uzdavinyte et al 2019;Schill et al 2019) and low-and middle-income countries (Tong and Kang 2019;Malik et al 2019), with mixed findings.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al. (2020) also found that the perceived risk of online purchase channels had a stronger negative impact on customer purchase behaviour than that of offline purchase channels. Considering these correlations and perceived risks, specific psychological studies may be conducted in the context of channels used by customers while purchasing green products.…”
Section: Future Research Agendamentioning
confidence: 98%
“…According to Perera and Hewege (2018), these perceived risks have restricted green purchases in many countries such as; Australia, Malaysia and Canada. The correlation between perceived risk and purchase behaviour has been found weakest in Asian countries and highest in European countries (Li et al., 2020). Li et al.…”
Section: Future Research Agendamentioning
confidence: 99%